Ultrasound-Responsive Nanobubbles for Combined siRNA-Cerium Oxide Nanoparticle Delivery to Bone Cells - Pedram Sotoudeh Bagha; Elayaraja Kolanthai; Fei Wei; Craig J. Neal; Udit Kumar; Gillian Braun; Melanie Coathup; Sudipta Seal; Mehdi Razavi (MDPI AG, 2023)
This study aims to present an ultrasound-mediated nanobubble (NB)-based gene delivery system that could potentially be applied in the future to treat bone disorders such as osteoporosis. NBs are sensitive to ultrasound (US) and serve as a controlled-released carrier to deliver a mixture of Cathepsin K (CTSK) siRNA and cerium oxide nanoparticles (CeNPs). This platform aimed to reduce bone resorption via downregulating CTSK expression in osteoclasts and enhance bone formation via the antioxidant and osteogenic properties of CeNPs. CeNPs were synthesized and characterized using transmission electron microscopy and X-ray photoelectron spectroscopy. The mixture of CTSK siRNA and CeNPs was adsorbed to the surface of NBs using a sonication method. The release profiles of CTSK siRNA and CeNPs labeled with a fluorescent tag molecule were measured after low-intensity pulsed ultrasound (LIPUS) stimulation using fluorescent spectroscopy. The maximum release of CTSK siRNA and the CeNPs for 1 mg/mL of NB-(CTSK siRNA + CeNPs) was obtained at 2.5 nM and 1 µg/mL, respectively, 3 days after LIPUS stimulation. Then, Alizarin Red Staining (ARS) was applied to human bone marrow-derived mesenchymal stem cells (hMSC) and tartrate-resistant acid phosphatase (TRAP) staining was applied to human osteoclast precursors (OCP) to evaluate osteogenic promotion and osteoclastogenic inhibition effects. A higher mineralization and a lower number of osteoclasts were quantified for NB-(CTSK siRNA + CeNPs) versus control +RANKL with ARS (p < 0.001) and TRAP-positive staining (p < 0.01). This study provides a method for the delivery of gene silencing siRNA and CeNPs using a US-sensitive NB system that could potentially be used in vivo and in the treatment of bone fractures and disorders such as osteoporosis.